2001
DOI: 10.2134/jeq2001.3051784x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Ammonium Concentrations in Surface Runoff from Grasslands Fertilized with Broiler Litter

Abstract: Application of broiler (Gallus gallus domesticus) litter to grasslands can increase ammonium (NH4-N) and dissolved reactive phosphorus (DRP) concentrations in surface runoff, but it is not known for how long after a broiler litter application that these concentrations remain elevated. This long-term study was conducted to measure NH4-N and DRP in surface runoff from grasslands fertilized with broiler litter. Six 0.75-ha, fescue (Festuca arundinacea Schreb.-)bermudagrass [Cynodon dactylon (L.) Pers.] paddocks r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
99
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 18 publications
5
99
1
4
Order By: Relevance
“…In a grazed bermudagrass/ tall fescue pasture in the Piedmont of Georgia, water runoff volume (13% of rainfall) was not affected whether pastures were grazed continuously or rotationally (3 days grazed and 21 days rested) 7 . During a total of 4 years of this same study, water runoff volume was 15 -4% of rainfall that occurred in 23 -5 events per year 8 . We have been investigating the effects of harvest and nutrient-source treatments on various soil, plant and animal responses in the Piedmont of Georgia to understand the relationships between productivity and conservation.…”
Section: Introductionmentioning
confidence: 78%
“…In a grazed bermudagrass/ tall fescue pasture in the Piedmont of Georgia, water runoff volume (13% of rainfall) was not affected whether pastures were grazed continuously or rotationally (3 days grazed and 21 days rested) 7 . During a total of 4 years of this same study, water runoff volume was 15 -4% of rainfall that occurred in 23 -5 events per year 8 . We have been investigating the effects of harvest and nutrient-source treatments on various soil, plant and animal responses in the Piedmont of Georgia to understand the relationships between productivity and conservation.…”
Section: Introductionmentioning
confidence: 78%
“…Previous research has shown that there is a direct relationship between STP and P concentrations in overland flow from noncalcareous and calcareous soil, and this relationship can be useful for environmental purposes (Pote et al 1999;Pierson et al 2001;Fang et al 2002;Torbert et al 2002). It has been noted that soil test P does not necessarily correlate well with P losses (Buczko and Kuchenbuch 2007).…”
mentioning
confidence: 99%
“…Pierson et al (2001) reportaron pérdidas anuales de 1.5 a 13.5 kg·ha -1 de N en la escorrentía, en el sur de Georgia, EE.UU. Estos autores indican que las pérdidas de nitrógeno dependen del volumen de la escorrentía y las concentraciones presentes del elemento.…”
Section: Introductionunclassified
“…Pierson et al (2001) reported annual losses of 1.5 to 13.5 kg·ha -1 of N in runoff in southern Georgia, USA. These authors indicate that nitrogen losses depend on the volume of runoff and concentrations of the element present.…”
Section: Introductionmentioning
confidence: 99%